2021
DOI: 10.1002/adom.202102157
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Ultraviolet C and Ultraviolet B Dual‐Band Persistent Luminescence by Manipulating the Garnet Structure

Abstract: PersL is a unique phenomenon that a material emits for an appreciable time (seconds, minutes, hours, or days) after switching off an optical excitation. Without the requirement of a continuous optical excitation, persistent phosphors in the visible and infrared ranges have been extensively studied during past decades and have shown a vast range of promising applications underlying the "persistence" feature, including night-vision displays, [22] bio-imaging, [23,24] and optical information storage. [25] Not unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…The interest toward deep-ultraviolet (UV) phosphors has recently tremendously grown in view of their potential utilization in tri-band-based light-emitting diodes (LEDs) for biochemical and medical applications. In particular, these materials can be used as so-called C, B, or A UV emission devices for catalyst and sterilization, whereas it has been shown that the sources operating in the C-UV range of 280–200 nm are preferred due to the most efficient germicidal effect. , Although rare-earth dopants in phosphors are the most widely used by now, the depletion of natural resources has driven the research efforts to the development of rare-earth-free substitutes suitable for emerging applications. These application needs have risen the issue of suitable materials.…”
Section: Introductionmentioning
confidence: 99%
“…The interest toward deep-ultraviolet (UV) phosphors has recently tremendously grown in view of their potential utilization in tri-band-based light-emitting diodes (LEDs) for biochemical and medical applications. In particular, these materials can be used as so-called C, B, or A UV emission devices for catalyst and sterilization, whereas it has been shown that the sources operating in the C-UV range of 280–200 nm are preferred due to the most efficient germicidal effect. , Although rare-earth dopants in phosphors are the most widely used by now, the depletion of natural resources has driven the research efforts to the development of rare-earth-free substitutes suitable for emerging applications. These application needs have risen the issue of suitable materials.…”
Section: Introductionmentioning
confidence: 99%
“…The past few decades have witnessed the rapid development of the long afterglow materials in both scientific research and industrial commercialization. In specific, the emergence of the SrAl 2 O 4 :Eu 2+ ,Dy 3+ phosphor has significantly improved both the intensity and duration of afterglow, leading to a successful application in many areas . In this case, Dy 3+ and Eu 2+ ions were codoped in a lattice and acted as a trap center and an emitting activator, respectively, which later inspired many afterglow works. Since then, codoping of two or more ionic species has become a major strategy for phosphor exploration.…”
mentioning
confidence: 99%
“…To our best knowledge, only a few persistent phosphors have been reported emitting in the UV range, including UVA (320-400 nm) PersL activated by Bi 3+ , [114][115][116][117][118][119][120][121][122] Pb 2+ , 9 or Tb 3+ , 123 UVB (280-320 nm) PersL activated by Pr 3+ 124,125 or Gd 3+ 126-129 and UVC PersL activated by Pr 3+ 40,41,129-131 or Bi 3+ 129,132 and dual-band UVC and UVB PersL activated by Pr 3+ . 53,133 Due to the high 4f5d energy state (the first case in Fig. 2a), Pr 3+ possibly absorbs ultraviolet irradiation via an allowed electric-dipole 4f 2 -4f5d inter-configurational transition.…”
Section: Uv Perslmentioning
confidence: 99%
“…Moreover, we recently demonstrated that Pr 3+ can be doped into the modified garnet crystal structure to achieve the UVC and UVB dual-band emission and PersL emission. 133,135 In the Pr 3+ -activated (Ca 1.5 Y 1.5 )(Al 3.5 Si 1.5 )O 12 , the PersL of Pr 3+ is not only at 266 nm but also at 313 nm, and both decays last for B12 h. The solar-blind imaging experiments assisted by this phosphor are discussed and other applications based on the dual-band UVC and UVB PersL capabilities are envisioned. As far as we know, it is the first reported dual-band UVC and UVB persistent phosphor.…”
Section: Uv Perslmentioning
confidence: 99%
See 1 more Smart Citation